Extraction, Isolation, Identification, and Characterization of Anthocyanin from Banana Inflorescence by Liquid Chromatography-Mass Spectroscopy and Its pH Sensitivity - Nuwanthi Senevirathna; Morteza Hassanpour; Ian O’Hara; Azharul Karim (Biomimetics)
Anthocyanin is an important flavonoid with antioxidant, anticancer, and anti-inflammatory properties. This research investigates the anthocyanin content of Cavendish banana inflorescence, a by-product often discarded as agricultural waste. The study employs two drying methods, namely oven-drying and freeze-drying, followed by accelerated solvent extraction using acidified water and methanol. Liquid chromatography-mass spectroscopy (LC-MS) results confirm banana inflorescence as a rich source of anthocyanins. According to LC-MS analysis, freeze-dried banana inflorescence extracted in methanol at 80 °C exhibits the highest anthocyanin content (130.01 mg/100 g). This sample also demonstrates superior characteristics, including a chroma value of 40.02 ± 0.01, a redness value of 38.09 ± 0.16, 18.46 ± 0.02 °Brix, a total phenolic content of 42.5 ± 1.00 mg/g, expressed as gallic acid equivalents, and a total antioxidant activity of 71.33 ± 0.08% when assessed with the DPPH method. Furthermore, the study identifies the predominant anthocyanin as cyanidin, along with the presence of other anthocyanins such as delphinidin (Dp), malvidin (Mv), petunidin (Pt), pelargonidin (Pg), and peonidin (Pn). Interestingly, the extracted anthocyanins demonstrate pH sensitivity, changing from red to brown as pH increases. These findings highlight the potential of utilizing Cavendish banana inflorescence for anthocyanin extraction, offering sustainable waste valorization methods with promising applications in biomimetics and bioinspiration fields.